Radiotherapy and hyperthermia for breast cancer patients at high risk of recurrence. (31st December 2022) - De-Colle, Chiara; Beller, Anna; Gani, Cihan; Weidner, Nicola; Heinrich, Vanessa; Lamprecht, Ulf; Gaupp, Stephan; Voigt, Otilia; Dohm, Oliver; Zips, Daniel; Müller, Arndt-Christian
Abstract: Purpose: To evaluate the long-term efficacy of combined radiotherapy (RT) and hyperthermia (HT) in a large mono-institutional cohort of breast cancer (BC) patients affected by recurrent, newly diagnosed non-resectable or high risk resected tumor. Materials and methods: Records of BC patients treated with RT + HT between 1995 and 2018 were retrospectively analyzed. RT doses of 50–70 Gy concurrent to a twice per week superficial HT were applied. For HT, a temperature between 41 and 42 °C was applied for approximately 1 h. Primary endpoint was local control (LC), secondary endpoints comprised toxicity, overall survival (OS), and progression-free survival (PFS). Results: A total of 191 patients and 196 RT + HT treatments were analyzed. In 154 cases (78.6%) RT + HT was performed for patients with recurrent BC. Among these, 93 (47.4% of the entire cohort) had received RT prior to RT + HT. Median follow up was 12.7 years. LC at 2, 5, and 10 years was 76.4, 72.8, and 69.5%, respectively. OS at 2, 5, and 10 years was 73.5, 52.3, and 35.5%, respectively. PFS at 2, 5, and 10 years was 55.6, 41, and 33.6%, respectively. Predictive factors for LC were tumor stage, distant metastases, estrogen/progesterone receptor expression, resection status and number of HT fractions. At multivariate analysis tumor stage and receptor expression were significant. No acute or late toxicities higher than grade 3 were observed. Conclusion: Combined RT + HT offers long-term high LC rates with acceptable toxicity for patients with recurrent, newly diagnosed non-resectable or resected BC at high risk of relapse.